Perancangan Standard Operating Procedure (SOP) Proses Produksi Virgin Coconut Oil (VCO) di UD Sari Kelapa Banyumas - Suri, Anita; Riandani, Andini Putri; Irfan, Yusuf (DPPM UNIVERSITAS PELITA BANGSA, 2022)
One of the MSMEs produced by VCO is UD Sari Kelapa. Production of VCO UD Sari Kelapa by fishing method. Currently, UD Sari Kelapa is experiencing inconsistent and uniform production results, therefore one of the solutions offered is the design of the Standard Operating Procedure (SOP) for the VCO Production Process. The purpose of this study is to arrange SOP for the VCO production process so that the products produced are consistent and uniform. The method carried out in this study is the data processing technique used, which is qualitative descriptive with several stages including: 1) data collection; 2) data reduction; 3) evaluation; 4) presentation of data; 5) conclusion. Determination and improvement of VCO production process in UD Sari Kelapa MSMEs includes the time of each stage of production, production equipment and product standards. The Standard Operating Procedure (SOP) of the VCO production process has been arranged in the form of a swimlane flowchart and narrative includes process units including raw material receipt units, production units, packaging units.